Autoimmune origin for immune checkpoint inhibitor-diabetes revealed by deep immune phenotyping of the pancreas - Todd M Brusko; Ana Luisa Perdigoto; Kevan C Herold; Zoe Quandt; Arabella Young; Garry Nolan; Jee Hye Kang; Mark S Anderson; Paul L Bollyky; Graham Larson Barlow; Jennifer A Smith; Irina Kusmartseva; et al. (Journal for ImmunoTherapy of Cancer)
Immune checkpoint inhibitor-diabetes (CPI-D) is an acute and non-resolving immune-related adverse event (irAE) initiated primarily by disrupting the programmed death-1 (PD-1)/programmed death-ligand 1 (PD-L1) axis with monoclonal antibodies. A major limitation in understanding CPI-D is the lack of access to pancreatic tissue from patients experiencing this complication. We report a unique patient with no prior history of diabetes or autoimmune disease whose treatment with CPI for metastatic melanoma was complicated by CPI-D requiring insulin therapy. The patient then went on to develop pancreatic cancer. In the setting of the pancreatic cancer treatment, we were able to perform detailed single-cell RNA sequencing and immunophenotyping within the surgically resected pancreas. This revealed substantial lymphocytic infiltration associated with the islets, suggestive of an autoimmune rather than autoinflammatory mechanistic origin for CPI-D.